2014
DOI: 10.1002/ijc.28949
|View full text |Cite
|
Sign up to set email alerts
|

An NMR metabolomics approach for the diagnosis of leptomeningeal carcinomatosis in lung adenocarcinoma cancer patients

Abstract: Leptomeningeal carcinomatosis (LC) is a metastatic cancer invading the central nervous system (CNS). We previously reported a metabolomic diagnostic approach as tested on an animal model and compared with current modalities. Here, we provide a proof of concept by applying it to human LC originating from lung cancer, the most common cause of CNS metastasis. Cerebrospinal fluid from LC (n 5 26) and normal groups (n 5 41) were obtained, and the diagnosis was established with clinical signs, cytology, MRI and bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…Efforts are underway to find a CSF biomarker from cancer-specific microRNA or metabolites that is an active initiator or specific byproduct of LMC123). We agree with those research trends, as we found that gross CSF profiles of cell counts and protein levels are poor indicators of LMC activity, especially when sampled from the ventricle.…”
Section: Discussionsupporting
confidence: 88%
“…Efforts are underway to find a CSF biomarker from cancer-specific microRNA or metabolites that is an active initiator or specific byproduct of LMC123). We agree with those research trends, as we found that gross CSF profiles of cell counts and protein levels are poor indicators of LMC activity, especially when sampled from the ventricle.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, given the dynamic nature of CSF production and C3a generation, we anticipate that CSF composition will be similarly in flux, and would be unlikely to achieve a steady state. Previous attempts to establish CSF biomarkers of metastasis including myo-inositol (An et al, 2015), β-microglobolin (Svatonova et al, 2014), and others (Walbert and Groves, 2010) have failed to prove useful across a diverse tumor types. Remarkably, we find that C3 is present in the CSF of patients with leptomeningeal metastasis from different types of cancer, and at levels above those of CSF from patients with brain parenchymal metastases or with no CNS metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis was made in 1 of 2 ways: (1) a CSF cytology positive for malignant cells, which was repeated up to three times or (2) MRI scans showing LC on both initial and 2-3 month follow-up studies in patients with suspicious cytology (atypical cells) or biochemical test (elevated protein level and/or decreased glucose level in CSF). 1,7,8,10,[16][17][18][19] The various MR imaging findings used for the diagnosis included superficial sulcal/cisternal enhancement, sulcal/cisternal obliteration, multiple tiny superficial nodules along the sulci/cistern, enhancement of cranial nerves, and hydrocephalus. 7,10 LC may grow in a linear pattern, creating a thin layer of cells spread diffusely over the brain surfaces, or in a nodular growth pattern, involving the leptomeninges in a multifocal skip pattern with intervening tumor-free areas.…”
Section: Diagnosis Of Lcmentioning
confidence: 99%
“…For the infratentorial area, it was scored as 0 (absent) or 1 (present). 19 In addition, other imaging parameters were also collected, including the presence and number of brain metastases, the presence of hydrocephalus, the pattern of LC (linear or nodular), and the location of LC in the brain.…”
Section: Image Analysismentioning
confidence: 99%